PKM PENGUSAHA TAHU SAYUR DAN KERIPIK TAHU KARANGREJO SELATAN DESA PURWOREJO KECAMATAN DONOMULYO KABUPATEN MALANG - Aminul Amin; Marli Marli (Publisher UPT P2M Politeknik Negeri Malang, 2019)
The purpose of the partners in establishing a tofu and tofu chip business is to increase family income and open up employment opportunities for the surrounding community because in the South Malang area most residents only rely on livelihoods from gardens that during the dry season cannot generate income. Besides partner regions, there are high poverty levels. Even though tofu suppliers in the market are abundant, there are still many gaps to reap the benefits of making tofu. Problems faced by partners related to the production process are tofu cooking equipment that has a small capacity, an inadequate production table, a manual tofu shredder, a small capacity frying device and very limited knowledge of bookkeeping and business management. The Community Partnership Program (PKM) is expected to be able to solve the problems faced by partners so that it will create a more efficient and more efficient tofu and vegetable tofu business so that in the future it can strengthen the national economy.